2017
DOI: 10.1158/1078-0432.ccr-16-1808
|View full text |Cite
|
Sign up to set email alerts
|

Heterodimeric IL15 Treatment Enhances Tumor Infiltration, Persistence, and Effector Functions of Adoptively Transferred Tumor-specific T Cells in the Absence of Lymphodepletion

Abstract: Purpose Adoptive cell transfer (ACT) is a promising immunotherapeutic approach for cancer. Host lymphodepletion is associated with favorable ACT therapy outcomes, but it may cause detrimental effects in humans. We tested the hypothesis that IL-15 administration enhances ACT in the absence of lymphodepletion. We previously showed that bioactive IL-15 in vivo comprises a stable complex of the IL-15 chain with the IL-15 receptor alpha chain (IL-15Rα), termed heterodimeric IL-15 (hetIL-15). Experimental Design W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 56 publications
(74 reference statements)
1
21
0
Order By: Relevance
“…hetIL-15 has an extended half-life in vivo and stimulates proliferation and cytotoxic commitment of NK cells and CD8 + effector T cells by binding to the IL-2/IL-15βγ receptor. We have shown that recombinant hetIL-15 induces proliferation, activation and increased cytotoxic potential of lymphocytes and, importantly, induces migration of lymphocytes into tumors in a murine model [ 25 ]. Due to these properties and its ability to delay tumor progression in animal models, hetIL-15 has progressed to clinical trials for metastatic cancer (NCT02452268).…”
Section: Introductionmentioning
confidence: 99%
“…hetIL-15 has an extended half-life in vivo and stimulates proliferation and cytotoxic commitment of NK cells and CD8 + effector T cells by binding to the IL-2/IL-15βγ receptor. We have shown that recombinant hetIL-15 induces proliferation, activation and increased cytotoxic potential of lymphocytes and, importantly, induces migration of lymphocytes into tumors in a murine model [ 25 ]. Due to these properties and its ability to delay tumor progression in animal models, hetIL-15 has progressed to clinical trials for metastatic cancer (NCT02452268).…”
Section: Introductionmentioning
confidence: 99%
“…Tregs in HIV-1-infected INR subjects and allowed dysfunctional cycling CD4 + T cells in INRs to complete the cell cycle and divide. These findings suggest that administration of IL-15, a cytokine in human trials for the treatment of cancer (50,51), could rescue functionally impaired Tregs, which bear features of an exhausted phenotype (52) in INR patients and enhance immune restoration in these subjects.…”
Section: Discussionmentioning
confidence: 91%
“…While TGF-β has come to be known for its roles in promoting tumor growth ( 152 ), suppressing T cell function ( 153 ), and enforcing Treg stability ( 154 ), its key role in T RM cell generation suggests its value in certain immunotherapy contexts. On the other hand, IL-15 has long been recognized for its role in supporting anti-tumor T cell responses ( 155 , 156 ). Studies show that T RM cells preferentially accumulate at sites of high IL-15 production, such as hair follicles in the skin ( 46 , 111 ).…”
Section: Optimizing T Rm Cell Responses For Cancermentioning
confidence: 99%